FURTHER OBSERVATIONS ON METACESTODIOSIS IN BLACK BENGAL GOAT IN BANGLADESH - Alim, M A; Islam, M K; Rahman, M M; Khan, M A H N A; Mondal, M M H (Biological Sciences - PJSIR, 2002)
Examination of 430 slaughtered Black Bengal goats, 198 male and 232 female,between 1 to 2.5 years of age, revealed 210 (48.84%) Cysticercus tenuicollis, 31 (7.21%) Coenurus cerebra/is and 5 (1.16%) mixed infection with C. tenuicollis and cerebra/is, while none of the goats had hydatid infection. The rate of infection was significantly (p<0.05) higher in female goats than in males. C. tenuicollis cysts were recovered from the peritoneum and mesentery. In case of cerebral coenurosis the C. cerebra/is cysts were found in the right and left cerebral haemispheres and median fissure of the brain . Besides from brain , coenurus cysts were also isolated from the diaphragm , subcutaneous tissues, the m uscles of the abdomen , intercostal , thigh and neck muscles. No marked pathological changes was observed due to C. tenuicollis. In case of cerebral coenurosis skull bone was thin and soft. Marked tissue reaction was observed in the muscular tissues infected with coenurus cysts. There was haemorrhages , necrosis and granulomatous reactions.